Bancassurance in Europe past, present and future - Fiordelisi, Franco 1972-; Ricci, Ornella 1982- (Palgrave Macmillan studies in banking and financial institutions, 2012)
This book offers a comprehensive view on bancassurance from its origin to future challenges and opportunities, considering the relevant changes currently interesting the financial services industry. It also provides a detailed review of theoretical and empirical literature dealing with financial conglomeration